Glacigenic sedimentation pulses triggered post-glacial gas hydrate dissociation - Jens Karstens (Nature Portfolio, 2018)
Triggers of gas hydrate instability along continental margins remain debated. Here, via numerical simulations, the authors show that pulses in sedimentation, rather than bottom water temperature or sea level change, likely triggered gas hydrate dissociation offshore Norway at the end of the last glaciation.